PENGARUH KARAKTERISTIK INDIVIDU DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT. PERTAMINA CABANG DENPASAR - Ida Ayu Chandra Regita Pidada; Gde Bayu Surya Parwita; I Nyoman Resa Adhika (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
Performance is the result of work carried out with the expected value. The purpose of this study was to determine the effect of individual characteristics and physical work environment on employee performance at PT. PERTAMINA Denpasar Branch. And to know simultaneously the influence of individual characteristics and physical work environment on employee performance at PT. PERTAMINA Denpasar Branch. This research was conducted at the office of PT. PERTAMINA Denpasar Branch which is located at JL. Sugianyar No. 10, Denpasar, Bali. The objects in this study are individual characteristics, physical work environment and employee performance. The population in this study are employees who work at PT. Pertamina Denpasar Branch as many as 42 employees. Determination of the sample in this study using a saturated sampling technique. Saturated sampling technique is a sampling technique using the entire population as a sample in the study because the population is less than 100. The analytical technique used in this study is Multiple Linear Regression Analysis. The results of this study are individual characteristics have a positive and significant effect on employee performance at PT. PERTAMINA Denpasar Branch, the physical work environment has a positive and significant effect on employee performance at PT. PERTAMINA Denpasar Branch, and individual characteristics and physical work environment simultaneously affect the performance of employees at PT. PERTAMINA Denpasar Branch.